Evaluation of the Frequency of Swine Enzootic Pneumonia in one Farm Based on Slaughterhouse, Clinical and Laboratory Monitoring - Sarturi, Janine Alves; Rossi, Carlos Augusto Rigon; Rech, Rodrigo Dalmina; Pinheiro, Analaura Bianchini; da Silva, Kauany Moura; Colpo, Ian Lovato; de Campos, Vitória Lima; Soares, Marcelo; Cargnelutti, Juliana Felipetto; Machado, Carolina Sleutjes (Acta Scientiae Veterinariae, 2021)
Background: Swine enzootic pneumonia (SEP), caused by the bacterium Mycoplasma hyopneumoniae, is one of the main respiratory diseases of pigs. The purpose of this study was to evaluate the frequency of SEP in one farm with an independent production system, low level of technification and high losses in the meat packing plant, based on slaughterhouse, clinical and laboratory monitoring. Materials, Methods & Results: This study consisted of three monitoring steps, divided into three periods: P1, P2 and P3. In the first step of the study, slaughterhouse reports were analyzed and slaughtering was monitored at one meatpacking plant in Santa Maria, RS, Brazil. The second step of the study started by drawing up a profile of the farm that supplied the pigs to the aforementioned slaughterhouse, after which clinical monitoring was performed on three occasions. The third step of the study (laboratory monitoring) involved collecting lung fragments containing suspected SEP lesions from the meatpacking plant and subjecting them analysis. The average measured enzootic pneumonia (EP) in P3 was 38.54% (P < 0.05) higher than in P1 and 29.79 higher than in P2. The mean frequency of pulmonary emphysema (PE) in P3 was 59.13% (P < 0.05) higher than in P1 and 48.04% higher than in P2. The mean number of lung adhesions (LA) did not differ statistically (P > 0.05) between P1, P2 and P3. As for the mean frequency of pulmonary hepatization (PH), P3 was 48.80% higher (P < 0.05) than P1 and 41.78% higher than P2. With regard to the mean frequency of craniodorsal lung lesions (CLL), P3 was 48.26% higher (P < 0.05) than P1 and 40.77% higher than P2. The mean frequency of disseminated lesions (DL) and the pneumonia severity index (PSI) showed no statistical difference (P > 0.05) between the three evaluated periods. On the other hand, in the finishing period (FP), the frequency of coughing and sneezing was 37.56% (P < 0.05) higher in P1 than in P3. The frequency of coughing and sneezing evaluated in the nursery phase (CF) did not differ (P > 0.05) between periods. The samples sent to the laboratory MicroVet tested positive for M. hyopneumoniae, Influenza virus and Pasteurella multocida capsular type A. In the samples sent to the laboratory LABAC, the mean PCRmo (PCR for identification of mollicutes) did not differ (P > 0.05) in the analyzed periods, although the presence of DNA from bacteria of the class Mollicutes was confirmed in the fragments. In addition, the mean results of PCRmy (PCR for identification of M. hyopneumoniae) also did not differ (P > 0.05), although they revealed positivity for M. hyopneumoniae. Discussion: In relationship to the mean frequency of PE in each analyzed period, our study revealed an increase in the number of pulmonary lesions at slaughter during the periods under analysis. This finding is in agreement with those of other authors, who explain that pneumonias is one of the main health problems for swine producers. Some lesions are identified more frequently in routine inspections in meatpacking plants, including pulmonary emphysema, lung adhesions and pneumonia caused by M. hyopneumoniae. In our study, we found that the clinical signs of respiratory distress decline between the periods under evaluation, but during slaughter, the lesions suggestive of SEP continued to show an upward trend, mainly because they were chronic. Other authors state that several control measures should be adopted to ensure good zootechnical indices, including vaccination, strategic medication and the reduction of risk factors, thereby minimizing the level of M. hyopneumoniae infection in the herd.